Estudo epidemiológico das vítimas fatais por acidentes de trânsito e ferimento por armas de fogo em nível pré-hospitalar, atendidas pelo SIATE, no município de Londrina-PR - Andrade, Maurício Edvalter (2010)
The increasing population, parallel to urbanization has brought to man, progress, but also the living with much intercurrence, which a lot of them increased to morbidity and even to mortality. Traffic accidents and violence represent modern epidemics that ravage countries from all the world, configuring a conjunct of health problems, high percentage of hospital confinement, besides that high hospital expenses, loss of goods and anguish for victims and their family. It is known, however, that educational and preventive measures can reduce morbidity and mortality from these causes, thus prevent damage to many families and expenses to the public coffers. Trying to understand some of the issues directly related to this problem, this study refers to the epidemiological study of all deaths in pre-hospital care to victims of traffic accident and injury by firearms, in the years 2007 and 2008, attended by service integrated trauma care and emergency (SIATE) in the municipality of Londrina. As the objective is to determine the profile of the fatal victims met, for such causes, in relation to gender, age and type of trauma, the incidence regions of Londrina city, opening period and to correlate these aspects. For this we sought the reports of Relatório de Atendimento do Socorrista (RAS), which are met by rescuers after observation of the data collected in each situation. The results revealed similarities between the total occurrences for the years studied, in both causes. The victims traffic acidentes 72.4%, of the victims were in death at the scene, 47.6% were using some type of protective equipment, (80%) were male ranging in age from 20 to 59 years (73.3) were the most frequent. The nature, 41% were due to collision and 31.4% for falls from bike, the period between 6:00 p.m. and 11:59 p.m recorded 45% of cases and the southern region accounted for 36.2% of cases. The location of the trauma was most often the skull (23.3%), followed by chest (18.1%). As for the results of accidents with firearms, was observed that 80.62% were in death at the scene, (94.57%) were male and aged between 20 and 34 years old (55.81%) were the most frequent. The period between 6:00 p.m. and 11:59 p.m. recorded 54.26% of cases and the North was responsible for 33.33% of cases, followed by the south (29.45%). The results point to the need for public safety policy and education, as most attended events could be prevented or make less drastic evolution. It is expected that the results provide subsidies to the city, police departments related to military and civilian, to enable them to develop and implement strategies to minimize such facts.